2018
DOI: 10.1007/s12649-018-0260-7
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of the Utilization of Waste Glycerol as an Addition to Wood Pellets

Abstract: Production of liquid biofuels derived from vegetable oils in recent years significantly increased which causes surplus of by-product (waste glycerol) from this process. Therefore it is of great importance to find cheap and fast method of use its utilization. In this study, a possibility of the utilization of technical purity glycerin as an addition to wood pellets intended for heating purposes has been investigated. Usefulness of pellets contained glycerol additions has been compared in terms of applicable qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In the transesterification reaction, triglycerides are converted, stepwise, to diglyceride, monoglyceride, and finally glycerol, which sinks to the bottom [31]. In addition, biodiesel that floats on top of the glycerol is an important byproduct and can be burned for heat or used as a feedstock in the cosmetic industry [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the transesterification reaction, triglycerides are converted, stepwise, to diglyceride, monoglyceride, and finally glycerol, which sinks to the bottom [31]. In addition, biodiesel that floats on top of the glycerol is an important byproduct and can be burned for heat or used as a feedstock in the cosmetic industry [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Bala-Litwiniak & Radomiak (2019) investigated the association between glycerine addition and ash content in wood pellets. The findings reported by those researchers show that the addition of glycerine at the weight rates of 2.0%, 4.5% and 7.0% led to reduced ash contents in the relevant pellets [66]. Chavalparit et al (2013) showed that the addition of glycerine is related to increased content of ash in the pellets [67].…”
Section: Resultsmentioning
confidence: 94%
“…When using oak wood sawdust, bulk densities of 222 kg/m 3 (Quercus rugosa) and 246 kg/m 3 (Quercus laeta), were reported [68]. On the other hand, an investigation revealed a density of 590 kg/m 3 for pine and fir wood pellets [69]. This density is of utmost importance for the transportation, handling and storage of densified biofuels [66].…”
Section: Bulk Densitymentioning
confidence: 99%